215P Evaluating the responsiveness of patient reported outcome measures (PROs) to change in valosin-containing protein multisystem proteinopathy (MSP1) over 24 months - Iammarino, M.; Reash, N.; Lowes, L.; Pietruszewski, L.; Adderley, K.; Humphrey, L.; Beale, A.; Steiner, C.; Smith, M.; Alfano, L. (Neuromuscular disorders : NMD, 2024)
As a growing number of experimental treatments move toward clinical trial in rare disease populations, The Federal Drug Administration (FDA) has placed an emphasis on documenting a patient's perception of their disease and the relationship of change with treatment. Currently, there are no disease-specific patient-reported outcome measures (PROs) for individuals with Valosin-Containing Protein Multisystem Proteinopathy (MSP1). The heterogeneity of MSP1 disease presentation and progression highlight the importance of exploring this area for clinical trial readiness. To determine the responsiveness to change in a selection of motor function PROs over 2 years; and to compare this change to that of functional outcomes. In this prospective, two-year natural history study subjects completed a selection of PROs and motor function testing at baseline, 12, and 24 months. The PROs included the PROMIS Upper Extremity (UE), Mobility, and Global Health scales; Rasch Overall ALS Disability Scale (ROADS); IBM Functional Rating Scale (IBMFRS); and Patient Global Impression of Change Scale. Nineteen subjects (age 28-66 years) with genetically confirmed MSP1 have completed all visits, with an additional four subjects having completed at least 12 months. Previously reported in this cohort, statistically significant changes in motor function testing were identified at both 12-month and 24-month time points. At 24-months, percent change in PROMIS Mobility and ROADS were significantly correlated to percent change in performance on mobility motor function assessments (Spearman's rho=0.64 and 0.56 with p-value<0.01 and 0.05, respectively). The IBMFRS and PROMIS UE were not sensitive to change over time in this cohort. Data collection is ongoing and updated analysis to be presented. Our study identified available PROs that demonstrate change consistent to change in motor performance over 24 months in this cohort. Inclusion of the patient perspective is key to successful interpretation of this and future trials in MSP1.